2015
DOI: 10.1016/j.actamat.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive study of phase transformation in age-hardening of Mg–3Nd–0.2Zn by means of scanning transmission electron microscopy

Abstract: The effects of thermal history on precipitation behavior and precipitation kinetics in Mg-3Nd-0.2Zn (wt. %) alloy were studied. The microstructure analysis of the aged alloys revealed the presence of new phases in the microstructure in addition to the old description: Super saturated solid solution (SSSS) → G. P. zones → β" → β'/β 1 → β, reported for Mg-Nd system. In this regard, the sequence of precipitation for the studied alloy was identified as: Super saturated solid solution (SSSS) → Clusters of atoms → G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…The aim of this study has been to resolve the :::: early studies [2,6,[9][10][11][12]. : We have shown that the early stages of the aging reaction in Mg-Nd alloys is dictated by the HCP convex hull.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this study has been to resolve the :::: early studies [2,6,[9][10][11][12]. : We have shown that the early stages of the aging reaction in Mg-Nd alloys is dictated by the HCP convex hull.…”
Section: Discussionmentioning
confidence: 99%
“…Mg-RE (rare-earth) alloys are especially attractive due to their high strength at peak aging conditions [2]. As a result, a number of recent studies have investigated the precipitation sequence [4][5][6][7][8][9] :::::: [4][5][6][7][8][9][10][11][12] and hardening mechanisms [13][14][15][16][17][18][19][20][21] in magnesium alloys. Nd has proven to be an important alloying element in this respect.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the strength of many age-hardened Mg-RE-Zr alloyscan be further enhanced by controlled addition of zinc (Zn) [5,15]. Smalladdition (< ~1 wt.%) of Zn promotes strength and creep resistance, while largeraddition (> ~1 wt.%) of Zn changes the prismatic ( 112 0 , or 101 0 ) β-series precipitates to basal ( 0001 ) γ-series, which are less effective in impeding basal dislocation motions [5].…”
Section: Introductionmentioning
confidence: 99%
“…Metals 2016, 6,196 3 of 10 Figure 2 shows the microstructure for Mg-2.7Nd-0.4Zn-0.5Zr alloy in as-cast condition. The microstructure of as-cast specimen consists of α-Mg matrix and eutectic compounds.…”
Section: Microstructuresmentioning
confidence: 99%
“…The precipitation sequence in this alloy during isothermal aging is commonly accepted as: supersaturated solid solution (SSSS) → ordered Guinier-Preston zones (G.P. zones) → β" → β → β 1 → β [6][7][8]. Despite many works regarding the precipitates evolution have been achieved in the past few years.…”
Section: Introductionmentioning
confidence: 99%